Autosomal recessive hypotrichosis with loose anagen hairs associated with TKFC mutations*. (1st May 2021) - Onoufriadis, A.; Cabezas, A.; Ng, J.C.F.; Canales, J.; Costas, M.J.; Ribeiro, J.M.; Rodrigues, J.R.; McAleer, M.A.; Castelo‐Soccio, L.; Simpson, M.A.; Fraternali, F.; Irvine, A.D.; et al.
Summary: Background: Loose anagen hair is a rare form of impaired hair anchorage in which anagen hairs that lack inner and outer root sheaths can be gently and painlessly plucked from the scalp. This condition usually occurs in children and is often self‐limiting. A genetic basis for the disorder has been suggested but not proven. A better understanding the aetiology of loose anagen hair may improve prevention and treatment strategies. Objectives: To identify a possible genetic basis of loose anagen hair using next‐generation DNA sequencing and functional analysis of variants identified. Methods: In this case study, whole‐exome sequencing analysis of a pedigree with one affected individual with features of loose anagen hair was performed. Results: The patient was found to be compound heterozygous for two single‐nucleotide substitutions in TKFC resulting in the following missense mutations: c.574G> C (p.Gly192Arg) and c.682C> T (p.Arg228Trp). Structural analysis of human TKFC showed that both mutations are located near the active site cavity. Kinetic assays of recombinant proteins bearing either of these amino acid substitutions showed almost no dihydroxyacetone kinase or D‐glyceraldehyde kinase activity, and FMN cyclase activity reduced to just 10% of wildtype catalytic activity. Conclusions: TKFC missense mutations may predispose to the development of loose anagen hairs. Identification of this new biochemical pathobiology expands the metabolic and genetic basis of hypotrichosis.